Perception towards genetically modified crops of the local farmers in Magalang, Pampanga, Philippines: a basis for an intervention program on GM crops - Pangilinan, Christian; Bagunu, Jacqueline (International Journal of Scientific World, 2015)
This descriptive research was undertaken to unveil the perception of the local farmers in Magalang, Pampanga towards GM crops with the aid of a written survey instrument administered to respondents from February to March 2014.In general, it was observed that despite inadequate information regarding GM crops, their implication and impact on human health, environment and economy, and their ambivalent view about the improved nutritional quality and other health benefits of GM crops, the farmers in Magalang, Pampanga consider GM crops safe for human consumption and a solution for food security. The respondents are very positive with regards to the improved yield and low production cost that these GM crops can offer. This suggests that the local farmers are primarily concerned with the quantity of produce as well as profit of their farming activity, their business and livelihood, rather than the quality of the produce in terms of effect on human health and the environment. Lastly, the local farmers are willing to accept, to adopt and to patronize GM crops. Findings from this research can serve as a basis for an intervention program that the local government or other organizations can initiate to address local farmers’ perception regarding GM crops.